2013
DOI: 10.1007/s11481-013-9512-2
|View full text |Cite
|
Sign up to set email alerts
|

Applications and Limitations of Inflammatory Biomarkers for Studies on Neurocognitive Impairment in HIV Infection

Abstract: Despite reduced prevalence of severe forms of HIV-associated neurocognitive disorders (HAND) on current antiretroviral therapy (ART) regimens, milder forms of neurocognitive impairment (NCI) remain prevalent in HIV-infected populations. These mild forms of HAND consist of subtypes, probably reflecting distinct, though possibly overlapping, pathophysiological mechanisms. Factors associated with HAND in HIV patients with prolonged viral suppression on ART include older age, low nadir CD4, active HCV co-infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 90 publications
(139 reference statements)
1
23
0
Order By: Relevance
“…Third, we did not measure sCD40L in plasma and thus its origin in CSF is uncertain. Fourth, the lack of relationship of GDS to other CSF inflammatory biomarkers was surprising but consistent with differences reported in prior studies 56 . We suspect that this variability may relate to differences in study populations, concurrent cardiometabolic variables, neurocognitive test instruments, or laboratory methods (multiplex versus single platform assays).…”
Section: Discussionsupporting
confidence: 87%
“…Third, we did not measure sCD40L in plasma and thus its origin in CSF is uncertain. Fourth, the lack of relationship of GDS to other CSF inflammatory biomarkers was surprising but consistent with differences reported in prior studies 56 . We suspect that this variability may relate to differences in study populations, concurrent cardiometabolic variables, neurocognitive test instruments, or laboratory methods (multiplex versus single platform assays).…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, associations among biomarker networks involved in chronic macrophage activation and vascular injury were seen among YLWH. sCD163 was associated with higher levels of sCD25, a known biomarker of macrophage, activation syndrome, and was also associated with sVCAM and CRP in conditions associated with vascular injury in both HIV and non-HIV associated conditions such as autoimmune disease [13, 23, 26, 3740]. While both sCD14 and sCD163 are associated with macrophage activation, the markers represent distinct pathways impacted by HIV; therefore, the lack of associations between these two biomarkers is not surprising but indicate complex effects by HIV infection on multiple innate immunity pathways [41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines and other inflammatory biomarkers have been clearly associated with HIV‐1‐associated dementia (HAD) in the pre‐cART era (Gartner and Liu, 2002; Glass et al, 1993; Perrella et al, 1992), but they may also play a role in the development of less severe forms of HAND despite viral suppression due to cART. A recent longitudinal study reported significantly higher levels of Interferon‐α‐2b, IL‐6, and sIL‐2R in HIV‐1+ individuals that became neurocognitively impaired, remained impaired, or worsened 1 year after the baseline study, compared to HIV‐1+ individuals who had either no impairment or improved neurocognitive status (Cassol et al, 2013). Neurocognitive impairment has also been associated with elevated levels of cytokines in perinatally HIV‐1‐infected children (Foster et al, 2012).…”
Section: Introductionmentioning
confidence: 99%